Glandular differentiation in pT1 urothelial carcinoma of bladder predicts poor prognosis - Zhao, Guobin (Sci Rep, 2019)
To evaluate the effect of glandular differentiation (GD) on tumor recurrence and progression of pT1 bladder urothelial carcinoma (UC). We performed a retrospective analysis of 82 bladder urothelial carcinoma with glandular differentiation (UCGD) patients which was pathologically diagnosed as pT1, 166 patients of pT1 UC of bladder without histologic variants served as controls. Patients of UCGD were more likely to have higher recurrence (P = 0.002) rate and higher progression rate (P < 0.001). Moreover, UCGD and a poor 5 -year overall survival (OS) (P = 0.02) while there was no difference in cancer-specific survival (CSS) (P = 0.062) between two groups. According to univariate analysis, largest tumor size (HR 1.502, CI 1.158–1.861, P = 0.029), UCGD (HR 1.787, CI 1.298–2.552, P = 0.001), lymphovascular invasion (LVI) (HR 1.226, CI 1.013–1.945, P = 0.039). UCGD (HR 1.367, CI 1.115–1.853, P = 0.038) and LVI (HR 1.416, CI 1.120–2.254, P = 0.013) were prognostic factors associated with disease recurrence and progression, respectively. Additionally, Additionally, UCGD significantly influence disease recurrence (HR 1.871, CI 1.338–2.589, P < 0.001) and progression (HR 1.462, CI 1.138–2.393, p = 0.007). Similarly, LVI significantly influence disease recurrence (HR 1.356, CI 1.053–2.174, P = 0.042) and progression (HR 1.348, CI 1.052–1.944, p = 0.022) in multivariate analysis. UCGD is significantly associated with higher recurrence and progression rate in patients with newly diagnosed pT1. Recurrent cases should be performed radical cystectomy (RC) earlier.